Letter (copy) : Safety of Spanish refugees - Citrine, Walter, 1887-1983
035-0100-001 Secretary's WMC/MMC/224. 1st December, 1942. Rev. A. Stewart, [8] Thistleton Avenue, Birkenhead, Cheshire. Dear Sir, Safety of Spanish Refugees. I am in receipt of your letter of the 27th November, and I share your anxiety concerning the safety of these men. I may say that I have already been in touch with the Foreign Secretary about the matter and urged that every step should be taken to secure that these men are not made the victims of indictive arrangements as a consequence of their activities during the Spanish Civil War. The position of the British Government in relation to the Spanish Government is, as you know, a delicate one, but I am hopeful that steps will be taken to ensure the safety of those who fought so heroically on the side of the forces of Democracy. Yours sincerely, General Secretary. 292/946/35/100